Skin and respiratory exposure to platinum group metals at two South African precious metals refineries - Linde, Stephanus J. L.; Franken, Anja; du Plessis, Johannes L. (International archives of occupational and environmental health, 2021)
Objective Platinum Group Metals (PGMs) are mined and refined together and have the potential to elicit adverse respiratory and skin health effects. The aim of this study was to investigate the simultaneous skin and respiratory exposure of precious metals refinery workers to all six soluble PGMs. Methods The simultaneous skin and respiratory exposure to soluble PGMs of forty workers at two precious metals refineries were measured over two consecutive work shifts using Ghostwipes™ and Methods for the Determination of Hazardous Substances method 46/2. Skin exposure was measured on the palm, wrist, neck, and forehead of workers. Results The highest geometric mean (GM) skin exposure (average of palm, wrist, neck and forehead) was found for soluble Pt (0.008 µg/cm 2 ) [95% confidence interval (CI) 0.005–0.013], followed, in order, by Rh, Ir, Pd, Ru, and Os. Significantly higher concentrations of soluble PGMs were found on the palm and wrist compared to the neck and forehead ( p < 0.0001). The highest GM respiratory exposure was found for soluble Pd (0.342 µg/m 3 [95% CI 0.163–0.718]) followed, in order, by Pt, Rh, Ru, Ir, and Os. Skin exposure to all soluble PGMs was positively correlated with respiratory exposure ( r = 0.466–0.702). Conclusion This is the first study to report skin exposure to all six soluble PGMs. Precious metals refinery workers were exposed to quantifiable concentrations of soluble PGMs via both the skin and inhalation. Exposure via both routes occurred together and control measures should be aimed at reducing both skin and respiratory exposure.